2021
DOI: 10.1158/0008-5472.can-21-2056
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of the 3D Genome Pinpoints Noncoding Drivers of Primary Prostate Tumors

Abstract: Prostate cancer is a heterogeneous disease whose progression is linked to genome instability. However, the impact of this instability on the noncoding genome and its three-dimensional organization to aid progression is unclear. Using primary benign and tumor tissue, we find a high concordance in higher-order three-dimensional genome organization. This concordance argues for constraints to the topology of prostate tumor genomes. Nonetheless, we identified changes in focal chromatin interactions, typical of loop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…This phenomenon has been termed 'enhancer hijacking' (Figure 2C). Further, SVs can disrupt the function of oncogenes and tumour suppressor genes via alteration of higher-order chromatin structure [141][142][143] (Figure 2D). A recent study by the PCAWG demonstrated that SVs affect topologically associating domain (TAD) boundaries in a cancer-specific manner (according to overall SV burden), are able to generate new TAD structures, and can lead to marked changes in chromatin folding [142].…”
Section: The Functional Impacts Of Structural Complexitymentioning
confidence: 99%
“…This phenomenon has been termed 'enhancer hijacking' (Figure 2C). Further, SVs can disrupt the function of oncogenes and tumour suppressor genes via alteration of higher-order chromatin structure [141][142][143] (Figure 2D). A recent study by the PCAWG demonstrated that SVs affect topologically associating domain (TAD) boundaries in a cancer-specific manner (according to overall SV burden), are able to generate new TAD structures, and can lead to marked changes in chromatin folding [142].…”
Section: The Functional Impacts Of Structural Complexitymentioning
confidence: 99%
“…There is controversy over the status of the higher-order chromatin organizations in prostate cancer. It has been suggested that the higher-order chromatin organization status in prostate cancer is stable relative to benign tissues, and the changes in local chromatin interactions mediate the development of prostate cancer [ 12 ]. Conversely, other studies suggest that the higher-order chromatin organization is disordered and co-exists with the change of epigenetic in prostate cancer [ 39 ], among which the factor CAF-1, which is involved in the conformation of the higher-order chromatin organization, is thought to be significantly associated with adverse biological behavior in prostate cancer [ 40 ].…”
Section: Chromatin-related Regulationmentioning
confidence: 99%
“…In particular, GSTP1 shows promoter hypermethylation in approximately 90% of PCa and 70% of prostatic intraepithelial neoplasia (PIN) patients [ 9 ]. In addition to DNA methylation, chromosome-related regulatory means such as histone modification [ 10 ], nucleosome localization [ 11 ], and higher-order chromatin organization [ 12 ] play important roles in the phenotypic transformation of prostate cancer. Recently, due to the breakthrough of high-throughput sequencing technology, the research for detecting RNA modifications has exploded [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using “normal” prostate epithelial cells and models of PCa (LNCaP and PC3), those so-called “normal” TADs were much larger, higher in number, and located in distinct positions [ 180 ]. However, low-input HiC from both primary PCa ( n = 12) and benign prostate tissues ( n = 5) demonstrated that, unlike cell lines, there was no significant difference in the number of TADs called or in TAD borders between samples [ 181 ]. Combining these data with whole-genome sequencing, they found only one structural variant (out of 260) with altered gene expression in an intra-TAD region.…”
Section: 3d Genome Organizationmentioning
confidence: 99%